(3GdehGRfGJ GdJbOjQjI (B:s (3OQhS hJeGQjf (B/s - (3TOQj, eYeQ SYGOs ((3GdLRGFQ(B: s (3GdfTQ GdLGeYj GdLOjO(B, s, 2021)
(3eaGgje Mhd GdehGRfGJ GdJbOjQjI , cPdc GdejRGfjI GdeGdjI, hecGfJgG aj eQGbHI GdJSjjQeY Tcd GdehGRfGJ GdJbOjQjI heQGMd GYOGOgG heHGODgG, HGdGVGaI Gdi GdehGRfI GdJbOjQjI ddeHjYGJ, JYQjagG eY CSGdjH JbOjQ ehGRfI GdeHjYGJ, cPdc GYOGOgG hGdQbGHI Ydi GdGfMQGaGJ aj ehGRfI GdeHjYGJ hJMdjdgG, HGdGVGaI Gdi GdehGRfI GdJbOjQjI ddGfJGL, eagheg hYdGbJg HehGRfI GdeHjYGJ, hGdehGRfI GdJbOjQjI ddJehjfGJhGdGSJKeGQGJeY GdehGRfI GdJbOjQjI ddNRjfIeaghegG hechfGJgG hGdeOI GdJj JZWjgGhNWhGJ GYOGOgG(B.s
(3eQGLY U(B.307-313s
Keywords: (3GdejRGfjI(B- (3eMGSHIs